Effects of psycho-scene-drama on empathic ability of patients with chronic schizophrenia. Issue 4 (1st December 2014) - Tian, Hongmei; Niu, Weifang; Liu, Ping; Wang, Na; Yu, Huijing; Zhao, Zhanhong
Abstract : Objective: The purpose of the current study was to determine the effects of psycho-scene drama on the empathic ability of patients with chronic schizophrenia. Methods: One hundred sixteen in-patients with chronic schizophrenia were randomly divided into study and control groups ( n =58 cases each). The original anti-psychotic drugs were not changed in either group. In the study group, the therapy was combined with psychological scene drama with a treatment course of 3 months. Before and after treatment, the interpersonal reaction index scale (Chinese version [IRI-C]), negative syndrome scale (SANS), social function assessment scale for patients with mental diseases (SSPI), Rosenberg self-esteem scale (SES), the emotional-social loneliness inventory (ESLI), and the Texas social behavior inventory (TSBI) were utilized for measurements. Results: A comparison of the IRI-C total, PT, FS, and EC factor scores before and after treatment in the study group was significantly different ( P <0.01); the PD factor score before and after treatment was not statistically significant ( P >0.05). A comparison of the IRI-C total score and each factor score before and after treatment in the control group was not significantly different ( P >0.05). A comparison of the IRI-C total, PT, and EC factor scores between the study and control groups after treatment was significantly different ( P <0.05). A comparison of the FS factor score between the study and control groups before and after treatment was significantly different ( P <0.01); the PD factor score was not significantly different ( P >0.05). A comparison of the SANS total, SSPI total, SES total, and ESLI total scores between the two groups after treatment was significantly different ( P <0.05). Conclusion: The psycho-scene drama can improve the empathic ability of patients with chronic schizophrenia, improve the negative symptoms and social function, increase the selfesteem and self-confidence, and reduce the loneliness in social interactions.